2010
DOI: 10.1371/journal.pone.0008581
|View full text |Cite
|
Sign up to set email alerts
|

Chk1 Haploinsufficiency Results in Anemia and Defective Erythropoiesis

Abstract: BackgroundErythropoiesis is a highly regulated and well-characterized developmental process responsible for providing the oxygen transport system of the body. However, few of the mechanisms involved in this process have been elucidated. Checkpoint Kinase 1 (Chk1) is best known for its role in the cell cycle and DNA damage pathways, and it has been shown to play a part in several pathways which when disrupted can lead to anemia.Methodology/Principal FindingsHere, we show that haploinsufficiency of Chk1 results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…To investigate this possibility, we generated a Pten +/− ;Chk1 +/− cohort of mice by crossing Pten +/− mice (38) with Chk1 +/− mice (3941). Pten +/− ;Chk1 +/− male compound mutants behave and age in a similar manner to their Pten +/− littermates (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate this possibility, we generated a Pten +/− ;Chk1 +/− cohort of mice by crossing Pten +/− mice (38) with Chk1 +/− mice (3941). Pten +/− ;Chk1 +/− male compound mutants behave and age in a similar manner to their Pten +/− littermates (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve high resolution in separating stages (4) through (9) of terminal erythropoiesis, we assessed c-kit 33 and CD44 34 markers along side the widely used combination of CD71 and Ter119. 35 We used the membrane-permeant SYTO16 nucleic acid dye to assess enucleation 36 (Supplementary Figure S4A). LSD1-kd caused an expansion of PreMegE (1), PreCFU-E (2) and, most strikingly, phenotypic CFU-E (3) progenitors (Figures 4a and b).…”
Section: Resultsmentioning
confidence: 99%
“…Disruptions of Chk1 by inhibitors may lead to anemia [18] as reported from a Phase I study of UCN-01 where all patients developed Grade 3 hyperglycemia and the observed DLTs were hyphosphatemia and anemia [19]. However, the present study with the administration of LY2603618 in combination with pemetrexed showed neither anemia nor hyphosphatemia as DLT, but a Grade 3 diarrhea was observed in one patient at 105 mg/m 2 , a Grade 3 fatigue in one patient at 195 mg/m 2 , a Grade 4 allergic reaction/hypersensitivity was observed in one patient at 150 mg/m 2 , and Grade 4 thrombocytopenia in two patients at 195 mg/m 2 .…”
Section: Discussionmentioning
confidence: 99%